(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2025)
In this thesis, the auditing organization should use three levels in assessing the reliability of the internal control system: high, medium, low. In order to improve the objectivity of the assessment of the reliability of the internal control system, the auditing organization should use other levels in addition to the above-mentioned levels. In foreign countries, they rate its reliability on a five-to-ten-point system, and some rate it as a percentage (0-100).